Adsorption and photocatalysis removal of arsenite, arsenate, and hexavalent chromium in water by the carbonized composite of manganese-crosslinked sodium alginate. (April 2022) - Mao, Wei; Zhang, Lixun; Zhang, Ying; Wang, Yanfei; Wen, Nuanling; Guan, Yuntao
Abstract: The preparation of easily synthesized and cheap composite materials for the efficient removal of toxic oxoanions still remains challenging in sewage treatment. Herein, a new carbonized manganese-crosslinked sodium alginate (Mn/SA-C) was fabricated for the removal of arsenite (As(III)), arsenate (As(V)) and hexavalent chromium (Cr(VI)) in water. The results indicated that the Mn/SA-C pretreated with MnSO4 solution (Mn/SA-C-S) exhibited a rapid adsorption toward As(III) and As(V) with the removal efficiency of >98% within 10 min, and had a high adsorption capacity toward As(III), As(V), and Cr(VI) with the maximum value of 189.29, 193.29, and 104.50 mg/g based on the Langmuir model, respectively. The removal efficiency of As(III), As(V), and Cr(VI) could be further significantly enhanced by coupling a photocatalytic process. For example, the time in which >98% of Cr(VI) (10 mg/L) was removed dramatically shortened from 360 min (adsorption) to 45 min (adsorption-photocatalysis), and the removal efficiency of As(III) increased by ∼10% within initial 5 min. This was primarily attributed to the Mn-catalyzed production of the photocatalytic excitons for Cr(VI) reduction, and the superoxide (O2 − ) and hydroxyl (OH) radicals for As(III) oxidation. The adsorption removal of arsenic (As) was primarily ascribed to surface complexation with MnO and precipitation by MnS2, and oxidative adsorption because of Mn valence cycle. The removal mechanisms of Cr(VI) mainly contained reduction by MnO and MnS2, complexation with MnO and carboxyl/hydroxyl groups as well as Cr(OH)3 precipitation. Our research provides a promising Mn/SA-C-S material for rapid and efficient removal of As(III), As(V), and Cr(VI) in contaminated water through an adsorption-photocatalysis synergistic strategy. Graphical abstract: Image 1 Highlights: A novel carbonized manganese-crosslinked sodium alginate (Mn/SA-C) was prepared. >98% of As(III) and As(V) was rapidly adsorbed within 10 min under dark condition. As(III), As(V) and Cr(VI) adsorption fitted well to pseudo-second-order models. The removal of As(III), As(V) and Cr(VI) was enhanced by coupling a photocatalysis. Adsorption-photocatalysis mechanisms of As(III), As(V) and Cr(VI) were proposed.